2021
DOI: 10.3389/fmolb.2021.687444
|View full text |Cite
|
Sign up to set email alerts
|

The Oncogenic Roles of JC Virus T Antigen in Breast Carcinogenesis

Abstract: Purpose: JC virus (JCV) infects 80–90% of the population and results in progressive multifocal leukoencephalopathy upon immunodeficiency. The study aimed to pathologically clarify the oncogenic roles of T antigen in human breast cancers.Methods: Breast cancer, dysplasia, and normal tissues were examined for T antigen of JCV by nested and real-time PCR. The positive rate or copy number of T antigen was compared with clinicopathological parameters of breast cancer. JCV existence was morphologically detected by i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
0
7
0
2
Order By: Relevance
“…Additionally, we for the first time found that JCPyV was less detectable in cervical epithelium than dysplasia and carcinoma (137). We also observed T antigen DNA and protein in hepatocellular, pancreatic, breast and cervical cancer cells using in situ PCR and immunohistochemistry (134)(135)(136).…”
Section: The Association Between Jcpyv and Carcinogenesismentioning
confidence: 88%
See 1 more Smart Citation
“…Additionally, we for the first time found that JCPyV was less detectable in cervical epithelium than dysplasia and carcinoma (137). We also observed T antigen DNA and protein in hepatocellular, pancreatic, breast and cervical cancer cells using in situ PCR and immunohistochemistry (134)(135)(136).…”
Section: The Association Between Jcpyv and Carcinogenesismentioning
confidence: 88%
“…In addition, we reported that the positivity rate and expression levels of T antigen were lower in breast cancer than in normal breast tissue (135), in line with hepatocellular and pancreatic cancer (136). T antigen DNA positivity was inversely associated with E-cadherin expression and triple-negative breast cancer but positively associated with lymph node involvement and ER and PR expression.…”
Section: The Association Between Jcpyv and Carcinogenesismentioning
confidence: 90%
“…VE6 in HPV16 and HPV18 promotes cell cycle deregulation leading to malignancy [63] . The large T antigen supports viral replication and carcinogenesis [64] , [65] . Functional enrichment analysis of this refined network showed that it is enriched in the cell cycle, apoptosis, and signaling pathways ( Supplementary Table S1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The viral etiology of human cancers is an interesting topic, and to date, several virus types have been identified in human cancers. JCPyV infects most of the world's population, with 80%-90% of adults being serum-positive [17]. Cell infection by JCPyV has two possible outcomes, including lytic infection in permissive cells that allows viral DNA replication and oncogenesis in nonpermissive cells, which do not support viral DNA replication resulting in incomplete infection or malignant cell transformation [18].…”
Section: Discussionmentioning
confidence: 99%
“…Cell infection by JCPyV has two possible outcomes, including lytic infection in permissive cells that allows viral DNA replication and oncogenesis in nonpermissive cells, which do not support viral DNA replication resulting in incomplete infection or malignant cell transformation [18]. Previous studies indicated a feasible role of JCPyV in several cancers, namely brain cancers of medulloblastomas and glial origin, as well as epithelial cancers, such as colon, prostate, breast, and lung adenocarcinoma, and esophageal carcinomas [10,13,17,19,20].…”
Section: Discussionmentioning
confidence: 99%